Eye for an Eye - Bache, Steve; Peter, Louise and Goudarzi, Mahyar (Germany : Film Academy Baden-Württemberg ; Aug&Ohr Medien, 2016)
Frederick Baer has spent over a decade on death row in Indiana State Prison for a crime committed in 2004. He is still waiting for his death penalty to be executed and this hand-drawn animation tells his story and highlights the conflicts he encounters regarding his guilt and destiny.
Verzio Film Festival Submission
Keywords: Documentary films